Crystallographic Benchmarking on Diffraction Pattern Profiling of Polymorphs-TiO2 by WPPF for Pigment and Acrylic Paint - Md. Mahmudul Kobir; Sumaya Tabassum; Shanawaz Ahmed; Sumaiya Islam Sadia; Md. Ashraful Alam (Archives of Current Research International, 2024)
At a very low temperature high crystalline phase of TiO2 best-fitted strain anatase was synthesized by peptization which was the prime object of this study. Unresolved parameters were investigated by the X-ray diffraction (XRD) technique employed for lattice parameters, crystallite size, lattice volume, strain, crystal structure, d-spacing and percentage of phase in weight fraction. 54.40 % anatase, 29.10 % brookite and 16.50 % rutile crystalline phase were found by whole powder pattern fitting (WPPF-Rietveld’s refinement) method and lattice volume of anatase 137.150, brookite 267.079 and rutile 62.901 Å³ as well the crystal strain 0.307, 0.45 and 0.28 % of anatase, brookite and rutile polymorph-TiO2 found respectively. The calculated lattice parameters of the anatase are \(α\)=\(β\)=\(γ\)= 90.0°; a=b= 3.8056 Å, c= 9.470 Å and predominant (101), (004) and (200) miller indices with diffracted angle (2Ɵ) 25.38, 37.26 and 48.22 observed. The average crystallite size was 7.39 nm which confirmed the formation of nano-crystal-TiO2 due to the highly dispersed on medium. The percentage of strain of the individual polymorphs of TiO2 shows the best fit used for the pigment and acrylic paint.